2022
DOI: 10.3233/jifs-220233
|View full text |Cite
|
Sign up to set email alerts
|

A novel intelligent cognitive computing-based APT malware detection for Endpoint systems

Abstract: Detecting and warning Advanced Persistent Threat (APT) malware in Endpoint is essential because the current trend of APT attacker groups is to find ways to spread malware to users and then escalate privileges in the system. In this study, to improve the ability to detect APT malware on Endpoint machines, we propose a novel intelligent cognitive calculation method based on a model combining graph embeddings and Attention using processes generated by executable files. The proposed intelligent cognitive computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, ML-based detection models have some quality issues, such as computational cost, accuracy, and time. Some studies used deep learning–based detection models to deal with massive amounts of data that required considerable storage and time for decision-making, such as [ 71 , 75 , 82 , 90 , 91 , 98 , 104 , 105 , 108 , 123 , 124 , 126 , [128] , [129] , [130] ]. Some studies that used AI-based detection models had problems such as delay, reliability, and computational costs, such as [ 70 , 72 , 74 , 77 , 79 , 122 , 131 , 132 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ML-based detection models have some quality issues, such as computational cost, accuracy, and time. Some studies used deep learning–based detection models to deal with massive amounts of data that required considerable storage and time for decision-making, such as [ 71 , 75 , 82 , 90 , 91 , 98 , 104 , 105 , 108 , 123 , 124 , 126 , [128] , [129] , [130] ]. Some studies that used AI-based detection models had problems such as delay, reliability, and computational costs, such as [ 70 , 72 , 74 , 77 , 79 , 122 , 131 , 132 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xuan and Huong [ 124 ] proposed a method to analyse and evaluate behaviour profiles using the Graph Isomorphism Network (GIN) to improve the efficiency of analysing and detecting APT malware on workstations. In addition, Xuan et al [ 129 ] proposed a new method for analysing and detecting APT malware on endpoint devices, such as unauthorised intrusions and insiders, using CNN-attention, a combination of CNN and the attention network. Further, Xuan and Duong [ 130 ] proposed a model that improves analysis efficiency and APT malware detection based on network traffic using CNN-LSTM and the attention network.…”
Section: Analysis and Findings Of Research Questionsmentioning
confidence: 99%
“…In some cases metrics like the code's entropy, number of characters, number of conditional sentences, among others, are applied [20], [28]. Other works also play with cyclomatic complexity [9], [20], use dependency and control flow graphs [10], [22], [24], [25], [27], [30]- [34], even work at token level [23], use vectors to represent assorted information [8], [19], [21], [26] or directly apply the code [29]. Once features are extracted, machine learning algorithms are used in all cases, being neural networks the most common one, specially MLP, though some works also use DNN, like [29].…”
Section: A Vulnerability Detectionmentioning
confidence: 99%
“…With this proposal, the authors improved some shortcomings of the proposal [ 25 ]. With the same approach of using the Attention network to build behavior profiles of APT attacks, in the study [ 33 ], the authors proposed a model combining deep learning networks with Attention networks to classify APT malware. However, we found that this model was still relatively complicated and cumbersome, and was difficult to implement in practice.…”
Section: Related Workmentioning
confidence: 99%